Structural Evaluation of Tied-Arch and Truss Footbridges through a Case Study - Imani, Mani Seyed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
Footbridges are usually slender structures with comparatively light load bearing requirements. These bridges are constructed over busy roads or other obstacles to provide a safe and easy passage for pedestrians and improve access. Footbridges are often less costly when compared to other bridges and structures. However, their aesthetics, appearance and practicability are also of high importance. The structure’s slenderness offer opportunities for engineering innovation, but these characteristics make designers pay more attention to issues, such as, wind, impact and collision loads. The main objective of this thesis is to propose some design alternatives for a footbridge crossing over Nicosia-Famagusta main road between the North and South Campuses of Eastern Mediterranean University. In this regard, two types of footbridges, tied-arch and truss bridges, with seven alternatives including the original bridge are investigated from four viewpoints; structural behavior, material usage, cost and aesthetics. Design and loading are according to AASHTO guidelines. Modeling and analyses of the structures are carried out by using the general purpose analyses and design program SAP2000, version 16.0.0 Ultimate. The footbridges studied in this research are to be constructed over a busy road, thus, the vulnerability of each alternative to impact and collision loads were investigated. For this purpose, progressive collapse analysis is carried out to study the behavior of design alternatives in case of damage to pier columns. The results showed that single span bridges have higher performances, and among them, arch type ones represent less deflection and lower compressive stress. In order to determine the bridge with the highest performance each of the investigated characteristics (structural behavior, material usage, cost and aesthetics) were first of all individually compared and then they were compared with each other. The results revealed that single span arch bridge that is designed to be constructed by using simple sections appear to be the best and most appropriate alternative if all parameters receive equal importance weights. However, assigning importance weights to the structural behavior, material usage, and cost, which are as three times as the one allotted to the aesthetics, resulted in selection of single span truss bridge as the most suitable option. Keywords: Footbridges, pedestrian bridges, structural behavior, progressive collapse analysis.

ÖZ : Üst geçitler diğer yapılara göre genelde daha narin yapılar olduğundan yük taşıyıcı sistemleri de hafif olur. Bu tür köprüler yoğun trafik olan yollarda ve yayaların geçişine engel oluşturan durumlarda yol ve engellerin üzerine inşa edilir ve yayaların güvenli ve rahat bir şekilde geçişini sağlar. Üst geçitler diğer köprü ve yapılara göre daha az maliyetli yapılardır. Fakat estetik görünümleri ve pratik olmaları büyük önem taşır. Yapının narin oluşu mühendislikte yaratıcılığa fırsat verirken bu özellik tasarımcının rüzgar, darbe ve çarpışma yüklerine de daha çok dikkat etmesini gerektirir. Bu tezin ana hedefi Doğu Akdeniz Üniversitesi kuzey ve güney yerleşkesi arasında kalan Lefkoşa-Mağusa ana yolunun üzerinden geçecek bir üst geçit için alternatifli tasarım üretmektir. Bu bağlamda iki tip üst geçit köprü tasarımı, bağlı-kemer ve makas köprü, mevcut üst geçit dahil yedi alternatif köprü olarak yapısal davranış, malzeme kullanımı, maliyet ve estetik görünüm açısından incelenmiştir. Tasarım ve yükleme AASHTO standardına göre yapılmıştır. Sözkonusu yedi alternatif üstgeçit köprüsünün modelleme ve yapısal analizi genel analiz ve tasarım programı SAP2000 Ultimate, 16. Versiyon kullanılarak yapılmıştır. Bu araştırma kapsamında incelenen üst geçitler yoğun trafik olan bir yol üzerine inşaa edilecektir, dolayısıyla her alternatif tasarımın, darbe ve çarpışma yüklerine karşı güvenirliği de çek edilmiştir. Bu nedenle üst geçit kolonlarında oluşabilecek bir hasar durumunda bahsekonu alternatif üstgeçit köprülerinin yapısal davranışı kademeli çökme analizi kullanılarak incelenmiştir. Elde edilen sonuçlara göre tek açıklıklı köprüler daha iyi performans göstermiş ve alternatifler arasında kemer tipi köprüler daha az sehim ve daha düşük basma gerilmesi elde etmişlerdir. Yapılan analizler sonucunda en yüksek performansı elde eden köprüyü bulmak için yapısal davranış, malzeme kullanımı, maliyet ve estetik görünüm özellikleri her bir köprü için önce ayrı ayrı karşılaştırılmış ve sonrasında da biribiriyle karşılaştırılmıştır. Karşılaştırmalar sonucunda yukarıda belirtilen dört özelliğin eşit önem ağırlığı alması durumunda tek açıklıklı, basit kesitlerle yapılmış kemer köprü en iyi performansı vermiş ve en uygun alternatif olmuştur. Diğer yandan yapısal davranış, malzeme kullanımı, maliyet özelliklerinin önem ağırlığının estetik görünüm özelliğinin üç katı olması durumunda tek açıklıklı, makas köprü en uygun alternatif olmuştur. Anahtar kelimeler: Üsgeçitler, yaya köprüleri,yapısal davranış, kademeli çökme analizi
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2014. Supervisor: Assist. Prof. Dr. Mürüde Çelikağ.
Keywords: Civil Engineering; Bridges - Design and Construction; Footbridges - Design and construction; Footbridges; pedestrian bridges; structural behavior; progressive collapse analysis